Changes in Microbiota Profiles After Prolonged Frozen Storage of Stool Suspensions - Dorsaz, Stéphane; Charretier, Yannick; Girard, Myriam; Gaïa, Nadia; Leo, Stefano; Schrenzel, Jacques; Harbarth, Stephan; Huttner, Benedikt; Lazarevic, Vladimir (Frontiers in Cellular and Infection Microbiology, 2020)
Introduction. Fecal microbiota transplantation (FMT) is recommended as safe and effective treatment for recurrent Clostridioides difficile infections. Freezing the FMT preparation simplifies the process, allowing a single stool sample to be used for multiple receivers and over an extended period of time. We aimed to assess the effect of long-term frozen storage on bacterial taxonomic profiles of a stool suspension prepared for FMT. Methods. DNA was extracted from a stool suspension before freezing and sequentially during the 18-month storage period at –80°C. Two different protocols were used for DNA extraction. The first relied on a classical mechanical and chemical cell disruption to extract both intra- and extracellular DNA; the second included specific pre-treatments aimed at removing free DNA and DNA from human and damaged bacterial cells. Taxonomic profiling of bacterial communities was performed by sequencing of V3–V4 16S rRNA gene amplicons. Results. Microbiota profiles obtained by whole DNA extraction procedure remained relatively stable during frozen storage. When DNA extraction procedure included specific pre-treatments, microbiota similarity between fresh and frozen samples progressively decreased with longer frozen storage times; notably, the abundance of Bacteroidetes decreased in a storage duration-dependent manner. The abundance of Firmicutes, the main butyrate producers in the colon, were not much affected by frozen storage for up to one year. Conclusion. Our data show that metataxonomic analysis of frozen stool suspensions subjected to specific pre-treatments prior to DNA extractions might provide an interesting indication of bacterial resistance to stress conditions and thus of chances of survival in FMT recipients.